Pyloric gland adenoma of the cystic duct with malignant transformation: Report of a case with a review of the literature - Schaefer, Inga Marie; Cameron, Silke; Middel, Peter; Homayounfar, Kia; Schwörer, Harald; Vieth, Michael; Veits, Lothar (BMC Cancer, 2012)
Background: Pyloric gland adenoma consists of closely packed pyloric-type glands lined by mucus-secreting cells. To date, approximately 230 cases have been reported, mostly of gastric localization with a tumour size up to 3.5 cm and a mean age of occurrence around 70 years. Adenocarcinoma develops in about 40% of cases and may be difficult to detect due to relatively mild nuclear atypia.Case presentation: We present the first case of a pyloric gland adenoma of the cystic duct in a 62-year-old male patient and demonstrate the clinicopathologic characteristics, including radiographic, molecular, and cytogenetic findings. The 2 cm-tumour developed in the cystic duct and protruded into the hepatic and common bile duct. On microscopic examination, it displayed closely packed pyloric-type glands, and focal architectural distortion with mild nuclear atypia. Immunohistochemically, it expressed MUC1, MUC5AC, MUC6 and p53, but not MUC2 and CD10. The Ki67-proliferation index was 25%. Furthermore, high-grade intraepithelial neoplasia was observed in the surrounding bile duct. We detected chromosomal gains at 7p, 7q11q21, 15q, 16p, 20, losses at 6p23pter, 6q, 18, and amplifications at 1q and 6p21p22 in the pyloric gland adenoma by comparative genomic hybridization. A KRAS codon 12 mutation (c.35G>T; p.G12V) was detected in the pyloric gland adenoma and in the adjacent dysplasia by sequencing analysis. The diagnosis of pyloric gland adenoma was established with transition into well-differentiated adenocarcinoma and high-grade biliary intraepithelial neoplasia.Conclusion: Pyloric gland adenoma evolving in the cystic duct is a rare differential diagnosis of obstructive bile duct tumours. Other premalignant bile duct lesions may be associated. Due to the risk of developing adenocarcinoma, surgical resection should be performed. © 2012 Schaefer et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Adenocarcinoma; Comparative genomic hybridization (CGH); Cystic duct; KRAS mutation; Pyloric gland adenoma